Signals evolution, learning, and information - Skyrms, Brian (Oxford : Oxford University Press, 2010)
Brian Skyrms offers a demonstration of how fundamental signals are to our world. He uses various scientific tools to examine how meaning & communication develop. Signals operate in networks of senders & receivers at all levels of life, transmitting & processing information. That is how humans & animals think & interact.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communication; Signs and symbols